Assemblage accumulation curves: A framework for resolving species accumulation in biological communities using DNA sequences. Issue 7 (18th April 2019) - van der Merwe, Marlien; Yap, Jia‐Yee S.; Bragg, Jason G.; Cristofolini, Caroline; Foster, Charles S. P.; Ho, Simon Y. W.; Rossetto, Maurizio
Abstract: The timing and tempo of the processes involved in community assembly are of substantial concern to community ecologists and conservation managers. The fossil record is a valuable source of data for studying past changes in community composition, but it is not always detailed enough to allow the process of community assembly to be resolved at regional or site scales while tracing the trajectories of known species with associated known traits. We present a three‐step framework for studying present‐day species accumulation through time: DNA sampling from multiple individuals from multiple species within a community; estimates of coalescence times for each species using molecular dating methods; and plotting the accumulation of present‐day species through time using the inferred population ages. Our approach is illustrated using whole‐chloroplast genomes from plants from three rainforest communities in eastern Australia. Expected times to coalescence for multiple species in each community were inferred from pooled high‐throughput sequence libraries. Local assemblage accumulation curves for each community were constructed. We also explored the variation in assemblage accumulation curves of species with different functional traits. Models of equilibrium species richness informed our null hypothesis and largely explained the shape of the assemblage accumulation curves. They indicated that the complexities of the accumulation process should be explored with additional parameters, for example, allowing species classes with different extinction rates. The assemblage accumulation curves for the study sites showed evidence of recent population expansions within each of the communities. This signal of recent accumulation is consistent with the increase in suitable rainforest habitat that followed the Last Glacial Maximum. Our method of constructing assemblage accumulation curves provides a simple approach for visualizing species accumulation data. It can be used to test hypotheses such as the relative survival potential of species‐specific ecological attributes. Although our example used single‐nucleotide polymorphisms derived from whole‐chloroplast sequencing, this framework can be applied to mitochondrial genomes and to communities of other organisms.